Quality of Life of Infants with Functional Gastrointestinal Disorders: A Large Prospective Observational Study - Jung, Camille; Beck, Laurence; Hanh, Thierry; Bellaiche, Marc (International Journal of Child Health and Nutrition, 2017)
Background: Functional gastrointestinal disorders (FGID) are very common during infancy, leading to frequent medical consultations. The aim of this large, prospective study was to assess the quality of life (QoL) and clinical management of infants with FGID. Methods: Completely or partially bottle-fed infants under 5 months old, presenting one or more FGID (regurgitation, constipation, diarrhea, crying/fussing), were enrolled during initial consultation by 111 pediatricians in private practice throughout France and reassessed at one month. Parents were asked to complete the QUALIN QoL questionnaire at inclusion and at Day 15. Results: A total of 815 infants (mean age 2.1±1.2 months) were evaluable. Mean QoL score improved from +27.2±15.1 at inclusion to +38.0±12.9 at day 15 (p<0.0001) irrespective of FGID symptoms. Multivariate analysis indicated that younger age, dietary advice, and partial breastfeeding were associated with better QoL outcome. Gastrointestinal symptoms showed significant regression at Day 30. The number of bottle feeds followed by external reflux episodes decreased from 80.0±27.4% to 36.1±31.4% at Day 30 (p<0.0001), the weekly number of stools increasing from 3.9±4.0 to 8.0±3.7 (p<0.0001). Conclusion: Medical management based on information, reassurance, lifestyle advice and dietary intervention improved QoL in infants with FGID and led to a reduction in FGID symptoms.